(untitled) (Estudios Gerenciales, 2013)
This article analyzes indicators of science and technology, showing the participation of the University ofCauca in the generation of network externalities. The methodology addresses quantitative and qualitativedesigns. Consists of a descriptive study that covers the main indicators of R&D and network externalitiesfrom the view of the specialized literature, and an analytical study that uses the technique known asmethod of consensus panel of experts. The answers of the experts are processed to determine the level ofconsistency and identify indicators of R&D that facilitate the measurement of network externalities, suchas the production of new knowledge-related products; number of networks through programs ofpostgraduates in national conventions; and number of graduates in specializations, master’s and doctoralprograms.